Investigation of Perovskite Solar Cells Employing Chemical Vapor Deposited Methylammonium Bismuth Iodide Layers. (10th July 2018) - Stümmler, Dominik; Sanders, Simon; Pfeiffer, Pascal; Wickel, Noah; Simkus, Gintautas; Heuken, Michael; Baumann, Peter K.; Vescan, Andrei; Kalisch, Holger
ABSTRACT: Although Pb-based perovskite solar cells already achieve power conversion efficiencies (PCE) beyond 20 %, the use of toxic Pb is causing considerable environmental concern. As a consequence, a variety of alternative cations have been investigated to replace Pb 2+ in the perovskite structure. Methylammonium bismuth iodide (MA3 Bi2 I9, MBI) has shown promising results for environmentally benign and chemically stable devices. While the PCE of MBI-based solar cells are still comparably low, structural improvements have been made by using chemical vapor deposition (CVD). CVD allows for the well-controlled formation of coherent and dense MBI layers in contrast to solution-processing. In this work, CVD as a possible MBI fabrication method for efficient and size-scalable solar cells is discussed. The precursors MA iodide (MAI) and Bi iodide (BiI3 ) are deposited in an alternating deposition process forming the desired MBI perovskite on the heated substrate. Substrate temperatures as well as deposition times of each precursor are varied with the aim of forming coherent and dense MBI layers. Optimized films are further processed to solar cell prototypes and compared with solution-processed reference devices. The results reveal that CVD possesses great potential to enable the manufacture of MBI photovoltaic (PV) devices processed in a solvent-free environment.